Predicting 1 year mortality after traumatic injury using the Clinical Frailty Scale. Issue 1 (8th October 2021) - Braude, Philip; Carter, Ben; Parry, Frances; Ibitoye, Sarah; Rickard, Frances; Walton, Ben; Short, Roxanna; Thompson, Julian; Shipway, David
Abstract: Background: Frailty is known to affect how people admitted with traumatic injuries recover during their inpatient stay and shortly after discharge. However, few studies have examined the effect of frailty on long‐term mortality when adjusted for significant factors including age. We aimed to determine the effect of frailty on 1‐year morality in older adults admitted with traumatic injuries. Methods: We undertook an observational study at the Severn Major Trauma Network's major trauma centre based in South West England. Patients ≥65 years old admitted between November 2018 and September 2019 with traumatic injuries were included. Isolated hip fractures and inpatient injuries were excluded. A geriatrician assessed all patients for frailty using the Clinical Frailty Scale. Follow‐up occurred at 1 year. A multivariable Cox proportional baseline hazards model assessed the effect of frailty on time‐to‐mortality. The adjusted model included age, sex, multimorbidity, surgery, most injured site, injury severity, postinjury complications, and geriatrician review. Results: Five hundred and eighty‐five patients were included. Median age was 81 years old (IQR 74–88), and median injury severity score was 13 (IQR 9–25). At 1 year 147 (25.1%) patients had died. Living with frailty was associated with mortality. The risk of dying increased with frailty severity. Compared to CFS 1–3: CFS 4 aHR = 1.73 (95% CI 0.89–3.36, p  = 0.11); CFS 5 aHR = 3.82 (95% CI 2.11–6.93, p  < 0.001); CFS 6 aHR = 4·05 (95% CI 2.21–7.45, p  < 0.001); CFS 7–8 aHR = 6.57 (95% CI 3.43–12.59, p  < 0.001). Conclusion: This study is the first to demonstrate a consistent effect of frailty, at all levels of severity and independent of age, on older peoples' survival 1 year after traumatic injury. These data support performing an admission frailty assessment to aid long‐term management decisions and provide opportunity to modify frailty to improve outcomes.